Arab and Jewish students in the post-Covid-19 era: Learning patterns as a trigger for dropout intent - Anat Raviv; Marsel Amasha; Noha Bader (Social Sciences and Humanities Open, 2023)
Following the COVID-19 pandemic, online academic courses continue to be offered by colleges (synchronous or asynchronous, distance learning or hybrid courses). As such, students are required to apply learning skills that differ from those used in traditional in-class lessons. This study examines students’ tendency to drop out of academia in light of such courses after social distancing has been eradicated, and their ability to develop suitable learning skills and self-regulated learning capabilities for successfully studying and completing such courses. The study included Arab and Jewish students from colleges and universities across Israel. The findings indicate that studying on online courses and hybrid courses (that combine both Zoom sessions and independent learning) have a significant impact on personal skills and learning abilities. These factors influence dropout rates as well. The findings of this study indicate that students need to undergo training for developing learning skills and tools that enable optimal self-regulated learning and self-management. Moreover, an emphasis should be placed on students from the Arab population, who are especially exposed to traditional forms of education in high school.